Implementasi Nilai-Nilai Pancasila Dalam Praktik Usaha UMKM dan Dampaknya Terhadap Preferensi Pelanggan: Studi Kasus Warung Nasi Teh Via Di Sindangsari, Kabupaten Serang - Muhammad Azmi; Daffa Muhamad Hidayat; Jiem’s Julian Saputra; Nuhiyah, Nuhiyah (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to analyze how Pancasila values are applied in MSME business practices and their impact on customer preferences with a case study of Rumah Makan Ibu Via in Sindangsari, Serang Regency. The approach used is descriptive qualitative through interviews, observation, and distribution of questionnaires to customers. The results show that the business owner consistently applies the principles of Pancasila, including honesty (first principle), respect for customers (second principle), cooperation with nearby merchants (third principle), openness to customer feedback (fourth principle), and fair and affordable pricing (fifth principl). The application of these values has a positive impact on customer satisfaction and loyalty, as seen in key preference factors such as affordable prices, a diverse menu, friendly service, and a comfortable location. Thus, the application of Pancasila values in MSME business practices not only serves as a moral and social guideline, but also contributes significantly to increasing customer loyalty and preference. The results of this study are expected to serve as an example of the application of national values in business practices for other SMEs in Indonesia.